Government Social Media Communication and Institutional Credibility: A Systematic Review of Elaboration Likelihood Model Applications in Tourism Governance - Lalu Muhammad Rifqi Nugraha; Maulina Pia Wulandari; Zulkarnain Zulkarnain (Universitas Sultan Ageng Tirtayasa, 2026)
The Elaboration Likelihood Model (ELM) has been widely applied in digital tourism communication research, yet its application to institutional credibility as a governance outcome remains largely unexplored. Most studies privilege place-centered outcomes such as destination image, treating the managing government institution as a transparent conduit rather than an actor whose legitimacy is publicly evaluated. This systematic review maps how ELM has been applied in digital tourism communication research from 2017 to 2026, with particular focus on whether institutional credibility has been examined as an organisation-centered governance outcome. Following PRISMA 2020 guidelines, systematic searches of Scopus and hand-searched sources yielded 31 articles after screening and full-text review. Thematic synthesis identified five clusters: ELM dual-route persuasion in tourism social media, digital storytelling and destination perception, influencer credibility and travel intention, information quality and eWOM, and digital content and behavioural intention. Only three of 31 studies explicitly examined institutional credibility as a governance outcome. The review identifies a critical theoretical gap and proposes a governance signalling framework connecting ELM’s dual-route mechanism to institutional credibility formation in public-sector digital communication.